Antiproliferative Action of Moringa oleifera Lam. Root Extracts in Acute Myeloid Leukemia (AML) Cell Line - Amr A. Nassrallah2, Khalid M. Aboul-Enein3, Hany A. El-Shemy2; Mutasim M. Khalafalla1, Eltayb Abdellatef1*, Hussein M. Daffalla (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: Moringa oleifera is a multipurpose plant, the fresh leaves may be cooked and eaten. The roots when mixed with water are used to treat malaria, hypertension, stomach disorders, to expel a retained placenta and to treat other health problems such as asthma and diabetes. To assess the antileukemia potency of different extract of Moringa oleifera roots (hot water, cold water and ethanolic extracts) were added to acute myeloid leukemia cell lines that harvested from adult patients to assess it is antiproliferative action using MTT assay. Among the different used extracts, ethanolic extract killed 51% of abnormal cells among primary cells harvested from 3 patients with Acute Myeloid Leukemia. In conclusion roots of Moringa oleifera contain active ingredients that were easily dissolved in ethanol and could be used as natural antitumor medicines.